A novel AMPK activator hernandezine inhibits LPS-induced TNFα production - Li, Ping (Oncotarget, 2017)
Here, we found that hernandezine, a novel AMPK activator, inhibited LPS-induced TNFα expression/production in human macrophage cells (THP-1 and U937 lines). Activation of AMPK is required for hernandezine-induced anti-LPS response. AMPKα shRNA or dominant negative mutation (T172A) blocked hernandezine-induced AMPK activation, which almost completely reversed anti-LPS activity by hernandezine. Exogenous expression of the constitutively activate AMPKα (T172D, caAMPKα) also suppressed TNFα production by LPS. Remarkably, hernandezine was unable to further inhibit LPS-mediated TNFα production in caAMPKα-expressing cells. Hernandezine inhibited LPS-induced reactive oxygen species (ROS) production and nuclear factor kappa B (NFκB) activation. Treatment of hernandezine in ex-vivo cultured primary human peripheral blood mononuclear cells (PBMCs) also largely attenuated LPS-induced TNFα production. Together, we conclude that AMPK activation by hernandezine inhibits LPS-induced TNFα production in macrophages/monocytes.